DETECTING DEPENDENCIES BETWEEN STATES OF MULTIPLE DATA STREAMS - Dragos, Stefan S; Vaida, Mircea F; Ureche, Cristian M; Suta, Loreta A; Voina, Alin (Acta technica napocensis. Electronică-Telecomunicaţii, 2013)
The subject of dependency detection has been addressed many times during the last 20 years, and methods that extract frequent patterns or temporal information from data have been developed. The information extracted has been used in fields like medicine, network surveillance, stock analysis and many others, thus proving its importance in real life. But as technology evolved, the amount of generated information grew to the point where storing it for later analysis was no longer an option. In this paper we propose a method of temporal dependency detection between states of heterogeneous data streams, that processes the information as it arrives and discards it afterwards, and we test it on real surveillance data. [PUBLICATION ABSTRACT]